Neuroscience education in Africa, prospects and challenges - Olabode Ekerin; Calistus Okechukwu K (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2021)
This review explores the scope of neuroscience education, the current and future trends and evaluates the limitations hindering the evolution of neuroscientific studies and research in Africa. Neuroscience is one of the most poorly addressed fields of study in Africa evidenced by the paucity of available data. Africa has a lot to do to improve neuroscience research. More government financing is needed if the continent's research sector is to continue to expand. International scientific collaborations are an important part of integrating into the global research community. African neuroscientists must also participate in policy and decision-making to urge governments to finance research into Africa's specific requirements.